Diseminasi Donor Darah dalam Mengembangkan Rasa Empati Mahasiswa Terhadap Sesama - Nur Avihani; Salwa Durrotun Nashah; Nafilatul Khusna; Lailatus Syifa Azzahro; Naila Zulfa Isnaini; Syarif Hidayatullah (Jurnal Pengabdian Masyarakat, 2024)
Blood donation dissemination is one of the progressive steps to educate the public in knowing and developing knowledge about blood donation so that they are motivated to donate blood, including students as agents of change. Students' lack of knowledge about blood donation is one of the factors that cause the low number of blood donors among students. The dissemination of blood donation activities in the university environment aims to educate students so that they can develop their empathy through blood donation activities after participating in blood donation dissemination activities. From the initial survey at the service location, namely UIN K.H. Abdurrahman Wahid Pekalongan, several problems were found, especially for students, namely failing the screening stage before blood donation due to low blood pressure, insufficient weight, and other instabilities that occur. The method used in this service is ABCD Approach, at the preparation stage which is carried out by coordinating by forming a committee in the service, then at the implementation stage education is carried out through direct blood donation dissemination to students, then the evaluation stage is a question and answer session.  This activity has the result of providing knowledge and developing students' knowledge about blood donation. Thus, students' awareness to apply tips and tricks to be able to do blood donation increases. So that a sense of empathy for others can be developed properly.